Persuasion strategies in the prophetic Hadith of tolerance: a cognitive linguistic perspective - Mariam Alzaidi; Bassil Mashaqba; Fatmah Aldahmani; Wadeema Aldhaheri; Samar Alsamahi (Cogent Arts & Humanities)
This study examines the persuasion strategies in the Prophetic Hadiths (PHs) on tolerance to identify the rhetorical and linguistic features used to make these Hadiths powerful. The study applied the cognitive and psychological Theory of Reasoned Action, along with Aristotle’s model of persuasion, to explore how language influences audience perceptions in the PHs. Three aspects shaping the persuasion process were observed: attraction (using appeals and linguistic strategies), evaluation (using beliefs, intentions and attitudes), and behaviour (social support and acceptance). The study found seven persuasion strategies applied in the PHs including showing distinction, honoring commitment, expressing solidarity, glorification, providing proofs, expressing authority, and proving success. Both expressing solidarity and authority were the most frequently employed strategies. Furthermore, the study revealed that along with the persuasive strategies, there was a great use of emotional, logical and moral appeals for their significance in affecting the audience’s positive evaluation. This study offers the first extensive examination of persuasive strategies in the PHs on tolerance by addressing the linguistic and rhetorical features, enhancing the understanding of their adequacy and relevance in developing moral behaviour which is useful for educational-, media-, and multi-religious communities.